2014
DOI: 10.1152/ajpcell.00271.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 3 is involved in intestinal epithelial cell apoptosis via N-(3-oxododecanoyl)-l-homoserine lactone-induced suppression of Akt phosphorylation

Abstract: N-acyl-homoserine lactones (AHL) are quorum-sensing molecules in bacteria that play important roles in regulating virulence gene expression in pathogens such as Pseudomonas aeruginosa. The present study compared responses between undifferentiated and differentiated Caco-2 cells to N-(3-oxododecanoyl)-l-homoserine lactone (3-oxo-C12-HSL). A low concentration of 3-oxo-C12-HSL (30 μM) is sufficient to reduce viability accompanied by apoptosis via the suppression of phosphorylation by Akt in undifferentiated Caco-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…7) However, we previously found that relatively low concentrations of 3-oxo-C 12 -HSL between 10 and 30 μM can induce the apoptosis of undifferentiated Caco-2 cells, and increase the mucosal permeability of the isolated rat colon. 8,9) Similar levels of 3-oxo-C 12 -HSL can be generated in culture supernatants of the P. aeruginosa PT149 strain without biofilm formation. 10) Therefore, 3-oxo-C 12 -HSL can affect intestinal epithelial cells at much lower concentrations than those found in biofilms.…”
Section: Please Scroll Down For Articlementioning
confidence: 92%
See 4 more Smart Citations
“…7) However, we previously found that relatively low concentrations of 3-oxo-C 12 -HSL between 10 and 30 μM can induce the apoptosis of undifferentiated Caco-2 cells, and increase the mucosal permeability of the isolated rat colon. 8,9) Similar levels of 3-oxo-C 12 -HSL can be generated in culture supernatants of the P. aeruginosa PT149 strain without biofilm formation. 10) Therefore, 3-oxo-C 12 -HSL can affect intestinal epithelial cells at much lower concentrations than those found in biofilms.…”
Section: Please Scroll Down For Articlementioning
confidence: 92%
“…Cell lysates were fractionated by SDS-PAGE and the proteins were transferred to Immobilon-P polyvinylidene fluoride membranes (Millipore, Bedford, MA, USA) for immunoblotting as described. 8) Phospho-ERK1/2 and phospho-Akt were normalized to total-ERK1/2 and total-Akt, respectively. Protein bands were visualized using the enhanced Chemi-Lumi One Super system (Nacalai Tesque Inc., Kyoto, Japan) and densitometrically analyzed using Lumi Vision PRO 400EX (Aisin, Kariya, Aichi, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations